2002
DOI: 10.1097/00000539-200203000-00039
|View full text |Cite
|
Sign up to set email alerts
|

Herbal Medicine Use in Parturients

Abstract: Herbal medicine use may be less prevalent in the parturient population, however, some health care providers may be promoting their use during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
71
0
5

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(87 citation statements)
references
References 18 publications
11
71
0
5
Order By: Relevance
“…Unser nicht repräsentatives Ergebnis mit dem Gebrauch mindestens eines Naturheilmittels von 684% der Schwangeren und Stillenden liegt nochmals deutlich hö-her und könnte durch die weite Definition des Begriffes «Naturheilmittel» bedingt sein, der auch Teedrogen einschloss, die bewusst oder unbewusst oft nicht als «Medi-zin» angesehen werden [11], was mit der eingangs erwähnten Assoziation von Naturheilmitteln mit «sanfter Medizin» zusammenhängen könnte. Ebenso ist ein Bias durch die Beschränkung der Befragung auf 3 Einrichtungen im innerstädtischen Bereich denkbar.…”
Section: Diskussionunclassified
See 1 more Smart Citation
“…Unser nicht repräsentatives Ergebnis mit dem Gebrauch mindestens eines Naturheilmittels von 684% der Schwangeren und Stillenden liegt nochmals deutlich hö-her und könnte durch die weite Definition des Begriffes «Naturheilmittel» bedingt sein, der auch Teedrogen einschloss, die bewusst oder unbewusst oft nicht als «Medi-zin» angesehen werden [11], was mit der eingangs erwähnten Assoziation von Naturheilmitteln mit «sanfter Medizin» zusammenhängen könnte. Ebenso ist ein Bias durch die Beschränkung der Befragung auf 3 Einrichtungen im innerstädtischen Bereich denkbar.…”
Section: Diskussionunclassified
“…Dies deckt sich mit Angaben, wonach etwa 73% amerikanischer Hebammen (North Carolina) ihren Patientinnen Heilpflanzenzubereitungen empfehlen [11,20].…”
Section: Diskussionunclassified
“…13 Also, in the study done by Hapner, 68.2% of participants used medicinal plants. 14 The study done by Planta suggested that 56% of persons used medicinal plants to remove their spiritual and physical problems. 15 Another study done by Jose et al 16 indicated that 9.8% of participants used medicinal plants within two weeks ago.…”
Section: Discussionmentioning
confidence: 99%
“…The authors finally asserted the need for more accurate knowledge about the efficacy and safety of herbal medicines in pregnancy (Holst, Wright, Haavik, & Nordeng, 2009). In addition, while patients generally take herbal supplements in combination with conventional drugs (Liu et al, 1997;Abebe, 2002), some researchers discuss that herbal medicines should be cautiously administered to prevent any possible adverse drug-herb interactions or complications such as bleeding (Hepner, 2002).…”
Section: Discussionmentioning
confidence: 99%